Design and investigation of novel neural stimulation by magnetic resonance coupling - Pradhan, Raunaq (2017)
Stimulation methods for treatment of neural disorders have evolved tremendously over the years ranging from invasive methods i.e. Deep Brain Stimulation (DBS) to non-invasive methods i.e. Transcutaneous Electric Nerve Stimulation (TENS) and Transcranial Magnetic Stimulation (TMS). This study hence first reviews existing literature for pain mechanism and how electrical stimulation is useful for treatment of pain. The existing commercial treatment options are analyzed to determine the technical drawbacks which could be overcome, to develop a more effective system for therapy. The proposed system comprises of a pair of coils, where current is induced in the secondary coil wirelessly and electric field is induced in the region between the coils due to magnetic resonance coupling. Addition of resonant structures and ferrite cores to this system has been studied, which enhanced the induced electric field (1.22 times due to addition of ferrite cores at 450 kHz source frequency). This study has been further extended for design and construction of a pair of figure-of-eight coils, coupled by magnetic resonance coupling (MRC), to generate (150 V/m per Ampere) electric field at the focal points for electromagnetic therapy related applications. For practical applications, which require adjustment of the focal point, a tri-mode coupled coil is proposed, where the focal adjustment of the E field can be optimized by tuning the current ratio across coils, which signify different modes of operation. A comparative study was also performed between the proposed magnetic resonant coupling (MRC) stimulation, magnetic stimulation (MS) and transcutaneous electrical nerve stimulation (TENS), in terms of the operating mechanism, ex-vivo tissue voltage measurement and electromagnetic simulation analysis. MRC RF stimulator was found to have several advantages compared to others to induce current in the biological medium for stimulation applications. These coils were then used for gene delivery in 3T3 cells, where they were able to achieve highly efficient transfection rates. Design and construction of MRC Figure of 8 coils, optimization of parameters depending on the application, and comparative advantages of the proposed technique over existing technologies has been the major contributions for this thesis. Besides, some of the future works and preliminary results in terms of new biomedical applications (drug delivery, gene delivery), improving the efficacy of the proposed system (magneto-acoustic stimulation) and future experiments (Von frey experiments for threshold determination of pain in mice) has also been highlighted.